Evaluation of the influence of cooling rate on residual strain development in unidirectional carbon fibre/polyphenylenesulfide laminates using embedded fibre Bragg grating sensors. (June 2017) - Tsukada, Takuhei; Takeda, Shin-ichi; Minakuchi, Shu; Iwahori, Yutaka; Takeda, Nobuo
This study investigates the influence of cooling rate on the residual strain of the carbon fibre/polyphenylenesulfide unidirectional laminates. Three different cooling rates (−300℃/min, −100℃/min and −10℃/min) were applied to simulate a wide range of cooling conditions. The crystallisation behaviour which depends on the cooling rate was evaluated using differential scanning calorimetry. A process monitoring test was then conducted using embedded fibre Bragg grating sensors. In-plane transverse strain of carbon fibre/polyphenylenesulfide unidirectional laminates was measured and the results were presented based on the crystallisation behaviour determined by differential scanning calorimetry. Furthermore, residual strain change after subsequent annealing was examined. This study successfully demonstrates the effectiveness of in situ process monitoring using fibre Bragg grating sensors for evaluating material behaviour of thermoplastic composites during rapid heating and cooling under realistic processing conditions.